Surface-initiated ring-opening polymerization of ɛ-caprolactone as a feasible approach to modify flax yarn. (January 2022) - Müller-Hülstede, J.; Schäfer, H.; Schiffels, P.; Bottke, P.; Wark, M.; Koschek, K.
Abstract: Surface-initiated ring-opening (SI-ROP) polymerization of ɛ-caprolactone is known as possible modification method to increase the hydrophobicity of cellulosic substrates. In this study SI-ROP of ɛ-caprolactone is applied on native and mercerized flax yarn. By use of triazabicyclodecene as catalyst, SI-ROP at room temperature was possible and poly-ɛ-caprolactone (PCL) was linked with a weight content of 4–10% to flax yarns. Besides a lower hydrophilicity an increased surface energy was achieved for PCL modified flax yarn. Furthermore, the positive effect of PCL linkage on the fibers surface regarding adhesion potential to an epoxy matrix was shown via conducting fiber-pull-out tests. After SI-ROP of ɛ-caprolactone on flax fiber surface a reduction of fiber pull-out up to 33% was achieved, evoked by physical improvement e.g. better wettability of fiber with epoxy matrix as well as enhanced crosslinking between the hydroxyl groups of the surface grafted PCL and the epoxy resin.